The archaeology of prehistoric burnt mounds in Ireland - Hawkes, Alan (Archaeopress Publishing Ltd, 2018)
This work details the archaeology of burnt mounds (fulachtaí fia) in Ireland, one of the most frequent and under researched prehistoric site types in the country. It presents a re-evaluation of the pyrolithic phenomenon in light of some 1000 excavated burnt mounds.